2020
DOI: 10.1029/2019gl083557
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stressing of Naturally Fractured Rocks: On the Relation Between Transient Changes in Permeability and Elastic Wave Velocity

Abstract: We report on laboratory experiments designed to explore the fundamental processes that impact fluid permeability during drilling and fluid injection. Coupled ultrasonic and permeability measurements are presented for Westerly granite samples fractured in situ and used to illuminate the relationship between nonlinear dynamic stiffness and fracture permeability indexed via fracture aperture. We perturb the effective stress field using normal stress and pore pressure oscillations. The velocity of ultrasonic waves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 63 publications
3
28
0
Order By: Relevance
“…Additionally, the elevated efficiency of the first stress perturbation in increasing permeability, as reported from the experiments by Candela et al 2015, is not observed in our experiments. A similar observation was recently noted also by Shokouhi et al (2019).…”
Section: Permeability Increase During 'Pure' Pressure Pulsessupporting
confidence: 89%
“…Additionally, the elevated efficiency of the first stress perturbation in increasing permeability, as reported from the experiments by Candela et al 2015, is not observed in our experiments. A similar observation was recently noted also by Shokouhi et al (2019).…”
Section: Permeability Increase During 'Pure' Pressure Pulsessupporting
confidence: 89%
“…Dynamic stresses may also enhance or reduce permeability by opening, closing or shearing cracks 15,132,141,[161][162][163] . Opening new cracks or widening already existing ones increases permeability whereas other fractures with less favourable orientations would be closed and hence decrease permeability.…”
Section: Triggering Mechanismsmentioning
confidence: 99%
“…The relationship between stress, strain, and elasticity is complex in individual rock samples 32,33 with mechanical damage and weak grain contacts being primarily responsible for nonlinear elastic behavior 34 . Temperature, pressure, and the presence of fluids modulate the nonlinear behavior 34,35 . In the Earth, seismic velocities are commonly observed to be faster when rocks are compressed, usually interpreted as the closing of 48 cracks 36,37 , while they are typically slower after experiencing strong shaking, usually interpreted as the breaking or weakening of internal contacts 38,39 .…”
Section: Rock Samples In Laboratory Experiments Typically Exhibit Animentioning
confidence: 99%
“…After the disturbance, the material relaxes back to its original or a new metastable state, the process of slow dynamics. Thus, rocks are 51 metastable in their elastic behavior and strongly influenced by relatively weak external forces 52 perturbing the material structure 35,38,39 .…”
Section: Rock Samples In Laboratory Experiments Typically Exhibit Animentioning
confidence: 99%